Expression of salivary hepcidin and its inducer, interleukin 6 as well as type I interferons are significantly elevated in infants with poor oral rotavirus vaccine take in South Africa - Mabasa, Vusumuzi; Seheri, Mapeseka L.; Magwira, Cliff A. (Frontiers in Immunology, 2025)
BackgroundThe metabolism of nutritional iron, required by viruses to replicate and proliferate, is regulated by hepcidin, a peptide hormone of 25 amino acids. Overexpression of hepcidin results in iron deficiency anemia (IDA), while its downregulation can lead to an iron overload. Recently, IDA has been highlighted for its role in the impairment of adaptive immunity and poor vaccine effectiveness. Here, we assessed the possible role of IDA in oral rotavirus (RV) vaccine take among South African infants.MethodologyPaired stool and unstimulated saliva were collected from oral RV vaccinated infants, who attended a routine immunization program at Oukasie Healthcare clinic, north of Pretoria, South Africa, to decide vaccine shedders (n = 20) and non-shedders (n = 18). IDA was determined by assaying the salivary hepcidin levels using an ELISA kit, while expression of hepcidin, hepcidin inducer IL-6, Interferon I (IFN I) and IFN-γ were determined by qPCR.ResultsThere were no significant differences in the average hepcidin levels between vaccine shedders and non-shedders (p = 0.83). Hepcidin levels were decreased 0.43-fold a week after vaccination versus pre-vaccination, p = 0.0001. Unlike the concentration, the expression of hepcidin increased 5-5-fold in non-shedders compared to vaccine shedders. Similarly, the expression of IL-6 and IFN I were increased 5.2- and 4.9-fold, respectively, in non-shedders compared to shedders. In contrast, the expression of IFN-γ was increased 3.2-fold in shedders compared to non-shedders.SummaryCollectively, our observations suggest a possible role for IDA in impediment of oral RV vaccine take among South African infants.